Characterization of Natural Clay from Gowa Regency, South Sulawesi Province, Indonesia - Sumiati Side; Suriati E. Putri (Universitas Tadulako, 2022)
Clay is one of the essential natural minerals in human life, especially in the industrial sector, which is widely used as a raw material for ceramics fabrication, adsorbents, and photocatalysts. The characteristics of clay significantly affect the quality of the resulting material. This study will study the aspects of natural clay in Gowa Regency, South Sulawesi Province, without the leaching process and with acid leaching. Acid leaching uses 3 M HCl, previously roasted at a temperature of 600 oC. The characterization consisted of metal oxide analysis using XRF, mineral content analysis using XRD, morphological analysis, and compound content using SEM-EDX. The results showed that the primary metal oxide content in natural clay was Fe2O3, Al2O3, and SiO2, the content of Fe2O3 decreased after the raw clay was treated with acid. The main mineral content in the sample is quartz, kaolinite, and hematite. The sample's morphology looks different after being given acid treatment; the acid leaching natural clay sample shows a porous morphology, while the natural clay without acid leaching shows the morphology in the form of lumps. The EDX mapping analysis showed that the number of impurities decreased after being given acid treatment.